Platelet to lymphocyte and neutrophil to lymphocyte ratios as strong predictors of mortality in intensive care population - Karagoz,Ibrahim (2019)
SUMMARY OBJECTIVE: Patients in intensive care units (ICU) have greater morbidity and mortality. We aimed to study neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) in the ICU population. METHODS: Medical and laboratory data of patients treated in ICU were retrospectively analyzed. Patients were divided into deceased and survived groups. RESULTS: The NLR of survived and deceased groups were 3.6 (0.2-31) and 9.5 (1-40), respectively (p<0.001). The PLR of the survived group (111 [16-537]) was significantly lower than the PLR of the deceased (209 [52-1143]), (p<0.001). An NLR higher than 4.9 had 84% sensitivity and 67% specificity is selecting deceased patients (AUC:0.80, p<0.001). A PLR higher than 112 had 83% sensitivity and 52% specificity in predicting deadly cases (AUC:0.76, p<0.001). Both PLR and NLR were significantly and positively correlated with c reactive protein levels. CONCLUSION: We suggest that physicians should pay particular attention to the treatment of patients in ICU with elevated NLR and PLR.